problems and challenges of research in the 21st century. (the case of the riems and the conformation of the anthropico) (Revista Electrónica REDINE, 2018)
The investigation(research) in the 21st century faces one without number of challenges and problems, in it(he, she) is century in which we live, the not alone challenge of the investigation(research) if not of the education, it(he, she) is that one must harmonize(reconcile) the matter and the spirit, the nature and the culture, the science and the humanities, propitiating(causing) a reunion between(among) the technology and the humanism, integrating(repaying) the memory(report) and the project. For it we believe that the new paradigm of the investigation (research) and education is the conformation of the antropoética. In this document we approach the problematics that represents the Integral Reform of the Average Top Education RIEMS(Educational policy adopted by the Federal Government to modify the Common Curricular Framework of the National Baccalaureate System (SNB) and which gives rise to agreement number 444, published on October 21, 2008 in the official newspaper of the Federation), not only for the investigation(research), but also for the process of conformation of the antropoética, for it his(her, your) conceptual terms(ends) are approached, since(as, like) antropoética, transverse competitions and the notions of conformation, complexity. We have selected the scene (stage) of the average top education, specifically the baccalaureate, for which it (he, she) is in this level of the education, where.
Keywords: antropoética; investigation; RIEMS; competitions; cross streets; complexity; average top education